Lexical and Syntactical Errors Performed by Junior High School Student in Writing Descriptive Text - Masruddin Masruddin; Nasriandi Nasriandi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study analysis the junior high school student’s lexical and syntactical errors in writing descriptive. This research applied qualitative research method. The source of data taken from the students writing. Those descriptive text were analyzed by classifying the error from two types of errors namely Lexical errors and syntactical errors. From this study, the researcher found lexical errors such as wrong spelling, false friend, the use of Indonesian word (code switching). While the syntactical errors namely error in pronoun, plurals, the use verb tense.